Constraints in the Adoption of Cage Aquaculture Practices in Ernakulam District, Kerala - Kappen, Daisy C; Dinesh, K; Divya, N D (Journal of Extension Education, 2019)
The Kerala University of Fisheries and Ocean Studies (KUFOS) implements a project entitled, “Village Adoption for Empowerment and Capacity Building Ensuring Livelihood of Fisherfolk in Central Kerala” from 2015 onwards with the objective of increasing fish production, creating employment opportunities to the fisher folk, thus ensuring livelihood security to them. The University is giving special emphasis on promoting cage aquaculture of variety of species in suitable areas and providing both technical and financial support to its beneficiary farmers for establishing small scale units. The present study was carried out in Ernakulam District of the Kerala State with the objective of identifying the constraints faced by 80 beneficiary farmers engaged in cage aquaculture of Asian seabass. The constraints faced by the cage aquaculture farmers were classified into three categories namely technical, economic and infrastructural/ administrative constraints. The most important constraints were non -availability of quality seeds, high cost of feed and lack of timely and adequate supply of seeds.